Analisis Konsep Probabilitas Dalam Matematika: Studi Literatur - Maryana Marpaung; Pera Novia Manurung; Juanda Rifki Simajuntak (Peneliti.net, 2026)
Probability is an important concept in mathematics that is closely related to various events involving uncertainty in everyday life. However, in the learning process of mathematics, students still experience several difficulties in understanding probability concepts comprehensively. Therefore, this study aims to analyze the concept of probability in mathematics and to examine students’ understanding, the difficulties they encounter, and learning strategies that can improve their comprehension of the concept. This study employed a literature review method by examining various scholarly articles related to probability in mathematics education. The data were analyzed using descriptive qualitative analysis through identification, review, and interpretation of theoretical concepts and findings from previous studies. The results of the review indicate that students’ understanding of probability concepts varies and is influenced by several factors, such as mathematical ability, learning experience, and students’ mathematical disposition. In addition, students often face difficulties in solving probability problems, including misunderstanding problem statements, translating problems into mathematical models, and interpreting the results obtained. Several learning strategies, such as the use of teaching aids, game-based learning, contextual approaches, and interactive learning media, have been shown to help improve students’ understanding of probability concepts. Therefore, probability learning needs to be designed in a more innovative and contextual manner in order to enhance students’ conceptual understanding and mathematical thinking skills.